The Nexus of Governance Indicators and Foreign Portfolio Investment (FPI): A Case Study of Pakistan - Zeshan Anwar; Maria Maria; Ayaz Qaiser; Muhammad Noman Nagra (STIM LASHARAN JAYA MAKASSAR, 2023)
FPI is a critical factor for growth of developing nations, therefore, this study aimed at examining the relation of governance factors with FPI inflows in Pakistan during the period of year 2001 to 2020 by the OLS model. The results have depicted that all the factors positively and significantly influence inflows of FPI in Pakistan except rule of law which have insignificant relationship with FPI. Therefore, the government should improve the governance level for improving the trust of overseas investors and improving FPI flows which would ultimately result in growth of Pakistan’s economy.